Sri Lankan sanitation policy adopts recycling of septage for reuse as fertilizer - CGIAR Research Program on Water, Land and Ecosystems (2017)
With WLE support, IWMI has played a highly influential role in preparing the 2017 Sri Lanka Sanitation Policy. IWMI developed the section on septage management including options for resource recovery and reuse of waste. 96% of all Sri Lankan households have septic tanks or latrines. These pose a significant environmental and health hazard if not appropriately treated. Reuse and recovery, when rolled out, will reduce these hazards as well as produce valuable recycled products such as organic fertilizer.